Current and emergent analytical methods for monitoring the behavior of agricultural functional nanoparticles in relevant matrices: a review. (September 2021) - Xu, Jie; Phillips, Rachel; Alarcon, Hugo; Kumar, Saurav
Abstract : Rapid expansion of ideas using engineered nanoparticles to achieve various agriculture-relevant functions (agri-NPs) over the past decade, has been revamping the available tools for studying these NPs in soil, plants, and irrigation-outflow (agri-matrices). The development of high-throughput analytical tools is imperative for defining the future scale of agri-NP applications. Here we summarized the available methods for studying the behavior and ecotoxicity of agri-NPs in relevant matrices, aiming to provide a comprehensive coverage of the latest progress in this field and to identify future-research urgencies. To render the readers with a general background of agri-NPs, we first introduced agri-NPs' various designated functions, materials, targets, and efficacy/environmental uncertainties. For future work, we propose to prioritize upgrading of existing in-situ tools for more diverse analytical capabilities, further development of higher-throughput screening methods that may enable automated data collection/analysis, development of more non-target analytical protocols, and extending the latest methods in biomedical-NP detection/quantification to study agri-NPs in plants.